Amazing Fish - Aysha Rau (Italy Ladybird, 2006)
There are lots of different types of fish and they all live in water.Take a journey underwater and find out more about them.With fascinating illustrations and clear font, this Level 1 Ladybird book is perfect for children who are ready to take their first steps in reading.
Keywords: Level Reader -- Level Reader